ANALYSIS OF DISTRIBUTION PATTERNS AND ACCESSIBILITY PRATAMA CLINIC HEALTH INFRASTRUCTURE NANGGALO DISTRICT, PADANG CITY - Aina Pahri; afdhal afdhal (JURNAL BUANA, 2025)
The pattern of distribution and accessibility of public health infrastructure in Nanggalo District will be easier to understand using spatial analysis. Analysis of distribution patterns and accessibility of primary clinic health infrastructure is needed for the purposes of supporting public health services. The nearest neighbor analysis method can be used in distribution patterns, buffers for service coverage and Network Service Area for travel distance. There are 6 Pratama clinics spread across Nanggalo District. Based on Nearest Neighbor calculations, the Pratama clinic distribution index was obtained with a value of 1.15, which had an uneven distribution pattern (random). Accessibility of pratama clinic services based on reach distance, the very close category with a distance of 0-100 m has an area of ​​16.25 ha (1.77%), the close category with a distance of 100-500 m has an area of ​​237.45 ha (25.92%), the medium category with a distance of 500-1000 m has an area of ​​375.21 ha (40.95%), and the far category with a distance of 1000-3000 m has an area of ​​287.35 ha (31.36%). Based on travel time, it takes 0-8 minutes to get to the nearest Pratama clinic from the residential area